PENGARUH POC AIR CUCIAN BERAS TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY - wiriani, Tirta; nurhayati, Nurhayati; rosmalinda, Rosmalinda (Politeknik Negeri Ketapang, 2023)
Rice washing water is one of the ingredients that has the potential to be used as liquid organic fertilizer because it contains nitrogen, phosphorus, potassium and vitamin B1 nutrients which have the potential as organic fertilizers that are still needed by plants. The area of ​​peatland in Indonesia is estimated at around 14.9 million ha, which has the potential to be used for agriculture. This study aims to determine the effectiveness of the nutrient content of POC rice washing water on the growth of oil palm seedlings in pre-nursary on peat soil. This study used a non-factorial Completely Randomized Design (CRD) with 5 treatments and 5 replications. Each treatment consisted of 3 plants so that 75 experimental units were obtained. Observation parameters consisted of plant height (cm), number of leaves (strands), stem diameter (mm), root volume (mL), and seedling dry weight (g). The data obtained were analyzed statistically by Analysis of Variance (ANOVA). If it is significantly different, then the Duncan Multiple Range Test (DMRT) will be further tested at the 5% level. The results showed that the concentration of 200 mL/liter of water was the best concentration for plant height parameters (cm), number of leaves (strands), stem diameter (mm), and seedling dry weight (g). While the concentration of 500 mL/liter of water can increase plant growth at the observed root volume (mL).